2018
DOI: 10.3390/molecules23112946
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Extraction Purification of Saliva Samples for Antipsychotic Drug Quantitation

Abstract: Saliva is far less popular as a diagnostic material than blood. This has resulted in a lack of procedures for the sampling and handling of saliva, e.g., effective ways to purify endogenous compounds from saliva to enable a simultaneous determination of xenobiotics such as neuroleptics. Therefore, the aim of this study was to develop an analytical procedure to purify saliva samples so that it is then possible to simultaneously determine five neuroleptics (aripiprazole, clozapine, olanzapine, quetiapine and risp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The methods for the determination of anti-epileptic drugs in blood have often been modified to determine carbamazepine in saliva [2,3,6,8,9,17,18]. Most often, saliva samples were 1 mL [14,18,22,23,25] or more [3,6,8], and were rarely less than 1 mL [15,21,24,27]. The method developed in this study allows for the determination of carbamazepine and its active metabolite, in as little as 200 µL of saliva.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The methods for the determination of anti-epileptic drugs in blood have often been modified to determine carbamazepine in saliva [2,3,6,8,9,17,18]. Most often, saliva samples were 1 mL [14,18,22,23,25] or more [3,6,8], and were rarely less than 1 mL [15,21,24,27]. The method developed in this study allows for the determination of carbamazepine and its active metabolite, in as little as 200 µL of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for the use of a small sample volume (200 µL). Preliminary studies showed that the use of Strata X-C columns, which were rinsed with water and a mixture of water and methanol (1:1), and saliva samples diluted with 2% formic acid solution and a mixture of water and methanol (1:1), is a good procedure for purifying saliva samples [22]. Applied to the analysis of neuroleptics and carbamazepine, it allowed for good saliva purification and an analysis of patient samples.…”
Section: Extraction With Phree Columnsmentioning
confidence: 99%
See 3 more Smart Citations